Fuzzy human development index: a numerical example of Southeast Asian countries - Abdullah, Lazim; Md. Tap, Abu Osman (2009)
One of the limitations of the widely used United Nation Development Program’s Human Development Index (UNDP-HDI) is that it does not taking into consideration the weights of each dimension. In spite of this, the index has been used to rank countries in the world. This paper proposes a framework that uses fuzzy set theory to offer the indices for each dimension. The fuzzy set approach employed in this paper incorporates the idea of lower and upper bound while retains the focus of the same dimensions without establishing a composite index. Results indicate that UNDP-HDI and fuzzy set based indices offer different countries rankings. This paper shows that some countries that have a high UNDP-HDI seemed to score low on a particular dimension of fuzzy indices. This raises important questions regarding the potential policy implications from the rankings.